2014
DOI: 10.1177/0093854814540287
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure of the Youth Psychopathic Traits Inventory

Abstract: The Youth Psychopathic Traits Inventory (YPI) assesses psychopathic traits cost-effectively while minimizing social desirability. To determine which YPI summary scores should be used, we tested (a) the factorial validity of its three scales and 10 subscales, (b) the fit of a new bifactor model, and (c) the measurement invariance of the best model across gender, age, and community/institutionalized samples. Three hundred ninety-five community adolescents (M age 15.8) and 200 institutionalized adolescents (M age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 69 publications
5
28
0
Order By: Relevance
“…The Impulsive-Irresponsible or Behavioral Dimension (BD) includes three subscales: Impulsiveness, Thrill-Seeking, and Irresponsibility. The YPI was designed to assess psychopathic traits in adolescence, and there is evidence that its 3-factor structure is invariant across adolescents from several ages (Pihet, Suter, Meylan, & Schmid, 2014). Importantly, several studies have supported the YPI’s factor structure (Neumann & Pardini, 2014), internal consistency and validity among young adults in their mid-20s (Campbell, Doucette, & French, 2009; Neumann & Pardini, 2014), while evidence suggests that a short version of the YPI is a suitable measure for longitudinal investigations focused on examining stability and changes in psychopathic traits during the transition into emerging adulthood (Colins & Andershed, in press ; Hawes, Mulvey, Schubert, & Pardini, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The Impulsive-Irresponsible or Behavioral Dimension (BD) includes three subscales: Impulsiveness, Thrill-Seeking, and Irresponsibility. The YPI was designed to assess psychopathic traits in adolescence, and there is evidence that its 3-factor structure is invariant across adolescents from several ages (Pihet, Suter, Meylan, & Schmid, 2014). Importantly, several studies have supported the YPI’s factor structure (Neumann & Pardini, 2014), internal consistency and validity among young adults in their mid-20s (Campbell, Doucette, & French, 2009; Neumann & Pardini, 2014), while evidence suggests that a short version of the YPI is a suitable measure for longitudinal investigations focused on examining stability and changes in psychopathic traits during the transition into emerging adulthood (Colins & Andershed, in press ; Hawes, Mulvey, Schubert, & Pardini, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Pihet et al (2014) recently showed that for the YPI, a bifactor model is superior in representing the data over a higher order model, when the 10 subscale scores of the YPI are used as the observed variables (i.e., the subscale level, see Figure 1). Pihet et al (2014) used data from a sample of 395 adolescents from the general population and 201 institutionalized adolescents and examined the factorial validity of the three dimensions and 10 subscales of the YPI. They compared six models with confirmatory factor analysis (CFA) using the 50 items of the YPI and three models using the 10 subscale scores as observed variables (i.e., subscale level).…”
Section: Factor Structuresmentioning
confidence: 99%
“…One of few studies testing for measurement invariance found that a subscale-based correlated factor structure provided a proper fit for both Dutch and Moroccan Dutch incarcerated boys (Veen et al, 2011). Moreover, in addition to testing the bifactor model, Pihet et al (2014) also examined the measurement invariance of the bifactor model using the subscale scores as observed variables for the YPI across gender, age, and community/institutionalized samples and established measurement invariance in all of these groups.…”
Section: Dimensionalitymentioning
confidence: 99%
See 2 more Smart Citations